Taxonomic study of species related to Anomala flavonotata Arrow, 1912, A. flavofasciata Arrow, 1912, and A. flavovaria Arrow, 1917 from the Himalaya and adjacent regions (Coleoptera: Scarabaeidae: Rutelinae) - Zhao, Ming-Zhi; Fujioka, Masayuki; Zorn, Carsten (Zootaxa, 2025)
The Anomala species from the Himalaya and adjacent regions with yellow and transverse band on elytra are revised, including Anomala flavonotata Arrow, 1912, A. flavovaria Arrow, 1917, A. flavofasciata Arrow, 1912, A. flaviventris Arrow, 1912 and A. brancuccii Sabatinelli, 1991. Additional twelve related species are described new to science, which are A. menyuensis Zhao, Fujioka & Zorn, sp. nov., A. spiniforceps Zhao, Fujioka & Zorn, sp. nov., A. luoyuensis Zhao, Fujioka & Zorn, sp. nov., A. latifasciata Zhao, Fujioka & Zorn, sp. nov., A. incurva Zhao, Fujioka & Zorn, sp. nov., A. bomiensis Zhao, Fujioka & Zorn, sp. nov., A. lhoba Zhao, Fujioka & Zorn, sp. nov., A. dilatostilus Zhao, Fujioka & Zorn, sp. nov., A. maedai Zhao, Fujioka & Zorn, sp. nov., A. suavis Zhao, Fujioka & Zorn, sp. nov., A. murzini Zhao, Fujioka & Zorn, sp. nov., and A. fenestrata Zhao, Fujioka & Zorn, sp. nov. Lectotypes are designated for A. flavonotata, A. flavovaria and A. flaviventris. Detailed descriptions, as well as figures of habitus and aedeagus are provided for all taxa.